Sistem Informasi Unit Pengumpul Zakat Terintegrasi (Studi Kasus: BAZNAS Kota Tasikmalaya) - Acep Irham Gufroni; Iwan Wisandani; Heni Sukmawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Zakat management in Indonesia is one of the interesting things to be studied in order to alleviate poverty and improve the welfare of the community, this can be seen from the potential IDR 217 trillion national charity but only reached about IDR 1.5 trillion. Factors affecting the collection of zakat in Indonesia is the level of trust muzaki against Zakat Organisation (OPZ) that in this study is a Zakat Collector Unit (UPZ), muzaki option to distribute zakat directly to mustahik individually, lack of knowledge of the mechanisms muzaki charity, and the lack of muzaki knowledge of the existence of UPZ. To address this problem, we need an information system that can organize management processes that occur in the management of UPZ-based charity, especially mosque-based UPZ, the mosque as a base because of it religious activities in the community. The method used is the analysis to direct UPZ location and design of the interface, rules, and prototype. From this study produced an Integrated UPZ and BAZNAS Tasikmalaya City Information Systems using web technologies.